The implementation of KH. Hasyim Asy’ari Thought About Educators Ethics - Azizah Hanum; Muh. Misdar; Faujiah Ramud; Nurliani (TADRIS: Jurnal Pendidikan Islam, 2021)
Ethic is important aspect in Islamic education. It’s existence is needed because it plays significant role to achieve the Islamic education goals. KH. Hasyim Asy’ari thinking about ethics educator starting from himself so well behaved. Then, taught the students when learning takes place. According of them, the educational purpose in every human being is to be a full human being in order to get closer to the Creator and get the happiness of the world and the hereafter. In the book Adab al-Alim wa al-Muta’alim, KH. Hasyim Asy’ari mention moralethical values ​should be the design of the people living in the world. So that a seeker of knowledge embody knowledge in everyday life with the behavior of resignation, wara’, the charity would please Allah, grateful and so on.